Effects of Trichostatin A on HDAC8 Expression, Proliferation and Cell Cycle of Molt-4 Cells - 何静 刘红利 陈燕 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
The effects of Trichostatin A （TSA） on histone deacetylase 8 （HDAC8） expression, proliferation and cell cycle arrest in T-lymphoblastic leukemia cell line Molt-4 cells in vitro were investigated. The effect of TSA on the growth of Molt-4 cells was studied by MTT assay. Flow cytometry was used to examine the cell cycle. The expression of HDAC8 was detected by using immunocytochemistry and Western blot. The results showed that proliferation of Molt-4 cells was inhibited in TSA-treated group in a time- and dose-dependent manner, The IC50 of TSA exposures for 24 h and 36 h were 254.3236 and 199.257 μg/L respectively. The cell cycle analysis revealed that Molt-4 was mostly in G0/G1 phase, and after treatment with TSA from 50 to 400 μg/L for 24 h, the percents of G0/G1 cells were decreased and cells were arrested in GJM phase. Treatment of TSA for 24 h could significantly inhibit the expression of HDAC8 protein in Molt-4 cells （P〈0.01）. It was concluded that TSA could decrease the expression of HDAC8 in Molt-4 cells, which contributed to the inhibition of proliferation and induction of cell cycle arrest in Molt-4 cells.